2012
DOI: 10.1038/mt.2012.145
|View full text |Cite
|
Sign up to set email alerts
|

AAV9-mediated VEGF-B Gene Transfer Improves Systolic Function in Progressive Left Ventricular Hypertrophy

Abstract: Mechanisms of the transition from compensatory hypertrophy to heart failure are poorly understood and the roles of vascular endothelial growth factors (VEGFs) in this process have not been fully clarified. We determined the expression profile of VEGFs and relevant receptors during the progression of left ventricular hypertrophy (LVH). C57BL mice were exposed to transversal aortic constriction (TAC) and the outcome was studied at different time points (1 day, 2, 4, and 10 weeks). A clear compensatory phase (2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 46 publications
2
44
0
1
Order By: Relevance
“…Thiazolidinediones also increase VEGF levels, which could be one reason for the fluid retention and congestive heart failure associated with these drugs (Baba et al, 2001; Gealekman et al, 2008; Soccio et al, 2014; Sotiropoulos et al, 2006). In contrast, VEGFB would provide a cardiovascular protective effect while maintaining the stability of blood vessels (Aase et al, 2001; Bellomo et al, 2000; Bry et al, 2010; Huusko et al, 2012; Kivelä et al, 2014; Lähteenvuo et al, 2009; Li et al, 2008a; Pepe et al, 2010; Serpi et al, 2011; Zentilin et al, 2010). In preclinical studies, VEGFB was identified as a promising candidate for the treatment of myocardial ischemia (Kivelä et al, 2014; Lähteenvuo et al, 2009; Pepe et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Thiazolidinediones also increase VEGF levels, which could be one reason for the fluid retention and congestive heart failure associated with these drugs (Baba et al, 2001; Gealekman et al, 2008; Soccio et al, 2014; Sotiropoulos et al, 2006). In contrast, VEGFB would provide a cardiovascular protective effect while maintaining the stability of blood vessels (Aase et al, 2001; Bellomo et al, 2000; Bry et al, 2010; Huusko et al, 2012; Kivelä et al, 2014; Lähteenvuo et al, 2009; Li et al, 2008a; Pepe et al, 2010; Serpi et al, 2011; Zentilin et al, 2010). In preclinical studies, VEGFB was identified as a promising candidate for the treatment of myocardial ischemia (Kivelä et al, 2014; Lähteenvuo et al, 2009; Pepe et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Increased left atrial pressure is closely related to diastolic dysfunction and it seems plausible that the relationships of VEGF-D with AF and heart failure share the same underlying mechanisms 20. Interestingly, VEGF-D has also been associated with left ventricular hypertrophy in mice, which is closely related to heart failure 21. However, although attenuated, there was still an association between VEGF-D and AF after adjustment for NT-proBNP.…”
Section: Discussionmentioning
confidence: 99%
“…123 An alternative promising strategy stems from the use of AAV vectors to overexpress diffusible growth factors, which can extend their effect beyond the individually transduced cells. Multiple intramyocardial injections of an AAV9 vector expressing VEGF-B, a member of the VEGF family that selectively binds VEGFR-1 expressed on cardiomyocytes, remarkably improved cardiac function in rats after myocardial infarction, 124 in mice after aortic constriction, 125 and in dogs chronically instrumented to develop tachypacing-induced dilated cardiomyopathy. 126 Diffusible factors such as insulinlike growth factor 1 were also shown to exert protective effect against cardiac dysfunction after secretion from a remote site, in particular on AAV5-mediated transduction of the skeletal muscle.…”
Section: Gene Therapy Of Heart Failurementioning
confidence: 99%